2021
DOI: 10.1089/jwh.2020.8491
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Use Cannabis for Gynecological Conditions: A National Survey

Abstract: Objective: Expanded legal access to cannabis in the United States has led to its increased use for treating medical conditions. We assessed the use of and attitudes toward cannabis for treating gynecological conditions. Materials and Methods: We utilized Amazon.com Inc.'s Mechanic Turk platform to administer a survey to U.S. women 18 years and older about cannabis use for recreational and medicinal purposes and willingness to use cannabis to treat 17 gynecological conditions. We collected sociodemographic data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Few similar surveys exist and these also appear to be open to bias. 34,35,36,37,38,39,40,41,42,43 There are very few high-quality studies evaluating the efficacy of cannabis-based compounds on endometriosis. A recent open-label study assessed pain scores in endometriosis patients treated with transpolydatin and palmitoylethanolamine (PEA) -an endogenous fatty acid amide with affinity to cannabinoid G-protein coupled receptors GPR55 and GPR119.…”
Section: Endometriosis and Cannabinoidsmentioning
confidence: 99%
“…Few similar surveys exist and these also appear to be open to bias. 34,35,36,37,38,39,40,41,42,43 There are very few high-quality studies evaluating the efficacy of cannabis-based compounds on endometriosis. A recent open-label study assessed pain scores in endometriosis patients treated with transpolydatin and palmitoylethanolamine (PEA) -an endogenous fatty acid amide with affinity to cannabinoid G-protein coupled receptors GPR55 and GPR119.…”
Section: Endometriosis and Cannabinoidsmentioning
confidence: 99%
“…This category captured participant's comments and awareness regarding driving after cannabis use, roadside drug testing and legal rami cations. Australia, as the rst country to introduce roadside drug testing laws [29], makes no distinction between medically prescribed or illicitly sourced cannabis when delta-9-tetrahydrocannabiniol (THC -the main psychotropic cannabinoid found in cannabis) is detected in point of collection bodily uid testing. The uncertainty around the legality of driving, even when they are not feeling impaired, was a signi cant concern to most women, as almost all had to drive due to either work or family commitments like dropping off and/or picking up children.…”
Section: Category 1: Not Many Optionsmentioning
confidence: 99%
“…[24,25] Historical medical evidence of cannabis being used to manage dysmenorrhea dates back to the 1800s, with Reynolds recommending its use in The Lancet in 1890. [26] Previous research by our team has found that many women in Australia [27] and New Zealand [28] with endometriosis report using cannabis, mostly obtained illicitly, to manage their menstrual and pelvic pain, and there is a signi cant willingness of women in the USA to use cannabis for gynaecological conditions, particularly those associated with pain [29]. However, very little is known about the suitability and acceptability of using cannabis to manage primary dysmenorrhea.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, few studies have examined cannabis use during labor and childbirth. 17 , 18 A recent descriptive study examined willingness to use cannabis during labor among Canadian women and found that one-third of women would consider using cannabis for labor pain. 18 However, this study was conducted before legalization of recreational cannabis in Canada in October 2018 and included women with vaginal deliveries only.…”
Section: Introductionmentioning
confidence: 99%
“…There is an additional U.S.-based study that examined cannabis use for gynecological conditions and asked about use during labor. 17 However, as this study was broadly focused on gynecological conditions, a detailed examination of willingness to use cannabis during labor was omitted. 17 Thus, there has yet to be a focused examination of women's attitudes toward cannabis use during labor in the United States, including the extent to which attitudes toward cannabis use during labor and willingness to use vary across states with different cannabis policies.…”
Section: Introductionmentioning
confidence: 99%